PENGUKURAN KINERJA KOPERASI CREDIT UNION DAYA LESTARI DI SANGATTA - Yusuf, Orva Septi (EKONOMIA, 2016)
Sustainable Power Cooperative CU in Sangata focus its efforts in the field of savings - loan, faced with competition from other general credit cooperatives. This demands of Sustainable Power Cooperative CU to implement good management. Sustainable Power Cooperative CU has implemented a management concept with the placement of employees according to their expertise, both in finance or marketing.However, to carry out the measurement of company performance, still using the traditional way, ie only see the effectiveness of the company's performance is based on the financial aspects without regard to other aspects. Formulation of this research is the performance of Sustainable Power Cooperative CU in Sangata measured with a balanced scorecard method to increase?Basic theory used is management accounting, data used kuangan report of Sustainable Power Cooperative CU in the form of Balance Sheet Sangata years 2013-2014 and 2013-2014 years of Business using a balanced scorecard analysis tool. The results showed seen from the perspective of financial analysis, it turns out the financial performance of Power Lestari CU good views of Return On Investment, Return On Equity, and Sales Growth unstable. Judging from the analysis of the customer perspective, the new customer, it appears that the performance is not stable. Judging from the Learning and growth perpective employee's performance turned out to have ups and downs this is indicated by the productivity of employees, employ rerention, the percentage of the cost of training and employee retention performance is unstable. Based on the results of the above conclusion, the hypothesis which states alleged that the performance of Sustainable Power Cooperative Credit Union in Sangata increase in 2014 if calculated using the balance scorecard, rejected.